2012
DOI: 10.1158/1535-7163.mct-12-0605
|View full text |Cite
|
Sign up to set email alerts
|

RSK2Ser227 at N-Terminal Kinase Domain Is a Potential Therapeutic Target for Multiple Myeloma

Abstract: Multiple myeloma is an entity of cytogenetically and genetically heterogenous plasma cell neoplasms. Despite recent improvement in the treatment outcome of multiple myeloma by novel molecular-targeted chemotherapeutics, multiple myeloma remains incurable. The identification of a therapeutic target molecule in which various signaling for cell-survival converge is a core component for the development of new therapeutic strategies against multiple myeloma. RSK2 is an essential mediator of the ERK1/2 signaling pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…39 RSK2 has also been shown to directly regulate proteins involved in apoptosis, such as BAD 40,41 and BIM. 16,42 In JJN3 cells, which have among the lowest baseline levels of IKZF1 (and thought to explain their inherent lenalidomide resistance), 8 IRF4 was not substantially downregulated by lenalidomide itself unless an RSK2 inhibitor was added. Unlike lenalidomide, treatment of MM cells with an RSK2 inhibitor alone does not appear to induce IKZF1 and IKZF3 degradation, and thus the mechanism of IRF4 depletion are complementary and nonoverlapping.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…39 RSK2 has also been shown to directly regulate proteins involved in apoptosis, such as BAD 40,41 and BIM. 16,42 In JJN3 cells, which have among the lowest baseline levels of IKZF1 (and thought to explain their inherent lenalidomide resistance), 8 IRF4 was not substantially downregulated by lenalidomide itself unless an RSK2 inhibitor was added. Unlike lenalidomide, treatment of MM cells with an RSK2 inhibitor alone does not appear to induce IKZF1 and IKZF3 degradation, and thus the mechanism of IRF4 depletion are complementary and nonoverlapping.…”
Section: Discussionmentioning
confidence: 99%
“…BI-D1870 is a selective RSK2 inhibitor previously demonstrated to induce cytotoxicity of myeloma cells through the inhibition of RSK2 activity. 16 Treatment of 4 HMCLs with BI-D1870 alone induced a dose-dependent cytotoxicity (supplemental Figure 4A). When HMCLs were treated with a combination of various doses of BI-D1870 and lenalidomide, a synergistic effect in inducing MM-cell cytotoxicity was observed ( Figure 3A and supplemental Figure 4B).…”
Section: Rsk2 Small Molecule Inhibitors Synergize With Lenalidomide Tmentioning
confidence: 96%
See 2 more Smart Citations
“…We have recently identified that the N-terminal kinase domain (NTKD) of RSK2, which is the most downstream signaling mediator of the RAS/ERK pathway in normal tissues, is universally activated thorough phosphorylation in myeloma cells with diverse cytogenetic/molecular abnormalities, regardless of the activation state of ERK and AKT (25). Importantly, the constitutive activation of RSK2-NTKD is responsible for the regulation of critical molecules for myelomagenesis, including c-MYC or CCNDs; however, the underlying mechanism for RSK2-NTKD in myeloma cells has not been identified (25).…”
Section: Introductionmentioning
confidence: 99%